2014
DOI: 10.1007/s11669-014-0345-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical Systematic Evaluation and Thermodynamic Optimization of the Mn-RE System (RE = Tb, Dy, Ho, Er, Tm and Lu) with Key Experiments for the Mn-Dy System

Abstract: Critical evaluation and optimization of all available phase diagrams and thermodynamic data for the Mn-RE (RE = Tb, Dy, Ho, Er, Tm, and Lu) systems has been conducted to obtain reliable thermodynamic functions of all the phases in the systems. Key experiments for the Mn-Dy system were performed using DSC and solution calorimeter. In the thermodynamic modeling, it is found that the Mn-RE systems show systematic changes in the phase diagrams and thermodynamic properties such as enthalpy of mixing in liquid state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 52 publications
(86 reference statements)
2
23
0
Order By: Relevance
“…using the modified quasichemical model to describe the liquid phase. Although the assessed Mn‐RE binary phase diagrams are consistent with the experimental data, the experimental heat capacities of the Mn‐RE intermetallic compounds (e.g., Mn 12 Tb, Mn 2 Tb, Mn 23 Lu 6 , Mn 2 Lu, Mn 12 Y, and Mn 2 Y) below 298 K were not taken into account in their assessments [18–20] . Furthermore, in order to develop a compatible thermodynamic database of the multicomponent RE‐Mn‐based alloy systems, the Mn‐RE binary systems still need to be reassessed considering all the experimental information, including phase equilibria and thermodynamic properties.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…using the modified quasichemical model to describe the liquid phase. Although the assessed Mn‐RE binary phase diagrams are consistent with the experimental data, the experimental heat capacities of the Mn‐RE intermetallic compounds (e.g., Mn 12 Tb, Mn 2 Tb, Mn 23 Lu 6 , Mn 2 Lu, Mn 12 Y, and Mn 2 Y) below 298 K were not taken into account in their assessments [18–20] . Furthermore, in order to develop a compatible thermodynamic database of the multicomponent RE‐Mn‐based alloy systems, the Mn‐RE binary systems still need to be reassessed considering all the experimental information, including phase equilibria and thermodynamic properties.…”
Section: Introductionmentioning
confidence: 93%
“…Three intermetallic compounds (Mn 12 Tb, Mn 23 Tb 6 , and Mn 2 Tb) were identified by the means of DTA, XRD, XRF, and metallography. However, Kim et al [18–20] . indicated that the results of the invariant reactions determined by Kirchmayr and Lugscheider [34] in the Mn‐Tb binary system are unreliable after comparing with the reported phase equilibria of the Mn‐Nd, Mn‐Gd, and Mn‐Dy binary systems.…”
Section: Literature Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The only experimental data available in the ternary and quaternary systems are partial phase diagram data at the Fe-rich corner of the Dy-Fe-B system and the section between the ternary magnetic compounds Fe 14 Nd 2 B and Fe 14 Dy 2 B. As highlighted in previous studies, 8,[10][11][12][13] the similarities and regularities in REcontaining systems can be used to predict phase diagram and thermodynamic data where no data are available. In the second part of this study, simulation of the RE extraction process from the Nd-Dy-Fe-B magnet by a liquid metal solvent is performed using the developed thermodynamic database.…”
Section: Introductionmentioning
confidence: 99%